Investigating hillslope afforestation as a potential natural flood management strategy in the Eddleston Water catchment, Scottish Borders - Sharp, Rosa (The University of Edinburgh, 2014)
Natural Flood Management (NFM) represents a sustainable alternative to traditional ‘hard- engineered’ flood defences. NFM has come to the forefront of environmental policy interest in recent years, particularly in light of projected increases in flood risk due to changes in climate and land use. Afforestation of hillslopes has been proposed as one such method of flood alleviation. However, the scientific evidence base for its effectiveness is limited. This project seeks to address this knowledge gap, in order to better inform policymakers and facilitate the development of efficient NFM strategies. Using a combination of empirical observations of rainfall-runoff relationships within the extensively monitored Eddleston Water catchment (69 km2) in the Scottish Borders, in addition to numerical modelling using the hydrological model HEC-HMS, I investigate the impact of current land use variations on the hydrological behaviour of three sub-basins within Eddleston Water. I then perform a series of simulations to assess the potential impact of afforestation both in these sub-basins and at the larger catchment scale. These analyses suggest that the existing variation in the hydrological response of sub-basins can be explained by differences in their physical characteristics, with the presence of forest cover resulting in reduced peak discharge. Furthermore, the model simulations suggest that afforestation of ~15% of the catchment produces a notable reduction in peak discharge at the catchment scale. Whilst uncertainties in the parameterisation of sub-basin characteristics limits the extent to which these findings can directly inform NFM policy, this project provides a starting point for future modelling studies, with recommendations made for further areas of research to reduce the uncertainty in the model experiments.
Keywords: Natural flood management; Hydrological modelling; MSc Environmental Sustainability